COMPATIBILITY OF RESPONSIBILITY ACCOUNTING AND THE PERFORMANCE-BASED ACTIVITY COSTING SYSTEM (PF-ABC) FOR IMPROVING COST MANAGEMENT - Hassoon, Hadeel Sameer; Abdullah, Nawfal Hussien (International Journal of Accounting Innovation, 2025)
Objective: This study aims to analyze the challenges inherent in traditional costing systems and to explore the integration of Responsibility Accounting and Performance-Focused Activity-Based Costing (PF-ABC) as contemporary approaches to enhance cost management and performance evaluation within industrial settings. Method: The research was conducted through an applied case study at the General Company for Electrical and Electronic Industries, focusing on the Electric Water Heater Production Line (80 and 120-liter models). Data were collected through on-site observations and financial performance analysis to identify inefficiencies and cost distortions. Results: Findings revealed that the manufacturing facility relied on outdated costing techniques, resulting in inflated production costs, frequent errors, and inefficiencies in operational processes. The application of Responsibility Accounting and PF-ABC demonstrated potential for more accurate cost allocation, enhanced managerial control, and improved performance evaluation. Novelty: This study contributes to management accounting literature by proposing a synergistic model that integrates Responsibility Accounting with PF-ABC, offering a modernized framework for cost management optimization and strategic decision-making in industrial enterprises.